Etnobotani Tumbuhan Pewarna Alami Kain Tenun pada Suku Baduy Luar Provinsi Banten - Mukhoyyaroh, Qiswatun; L. S. Nugraheni; N. Utami (Program Studi Pendidikan Biologi, FKIP Unpas,, 2023)
This research aims to identify the types, habitus, parts/organs and processing methods of plants used as natural materials for woven cloth from the Outer Baduy Banten tribe. Apart from that, this research also aims to identify the colors produced from plants used as natural materials for the woven cloth of the Baduy Luar tribe. The research approach uses quantitative with exploratory survey methods. Determination of the sample using purposive sampling technique. The samples chosen were deliberately determined based on certain criteria, namely someone who understands the dyeing of woven fabric in the Baduy community and someone who understands weaving techniques in the Outer Baduy tribe. The number of samples from the Outer Baduy tribe was 5 people. The results of the research show that the natural dye plants found in the Outer Baduy tribe are 9 types of plants, consisting of 8 families, 3 habituses (trees, bushes and shrubs), 5 plant organs that are used (bark, leaves, rhizomes, stems and roots), The majority of processing methods involve boiling the parts of the organs used and then soaking them, the resulting colors are yellow, blue, brown, red and black.